Evaluating ERP System Success Through the DeLone and McLean Model in Financial Organizations - Muhammad Darriel Aqmal Aksana; Arista Pratama; Siti Mukaromah (Komunitas Dosen Indonesia, 2025)
Enterprise Resource Planning (ERP) systems play a crucial role in streamlining business operations and enhancing organizational efficiency. However, their success largely depends on effective user engagement and system utilization. Despite being strategically implemented to support daily operations, many ERP systems face challenges such as technical errors, sluggish performance, inaccurate data, and poor user interfaces—factors that hinder optimal usage and reduce employee productivity. This study evaluates the success of an ERP system implemented in a financial services organization in Indonesia, focusing on employee perspectives to understand critical factors influencing system effectiveness. The DeLone and McLean Information Systems Success Model (ISSM) is employed as the theoretical framework, assessing six core constructs: System Quality, Information Quality, Use, User Satisfaction, Individual Impact, and Organizational Impact. A quantitative survey was conducted with 325 respondents selected through simple random sampling from key operational divisions. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results confirm that Information Quality has a significant effect on both system Use and User Satisfaction, while System Quality strongly affects User Satisfaction. Furthermore, User Satisfaction substantially influences both Use and Individual Impact. Most critically, Individual Impact has a pronounced and statistically significant influence on Organizational Impact (R² = 0.745). These findings emphasize the pivotal roles of information accuracy and user satisfaction in ensuring ERP success. The study provides valuable insights into how employee experience with ERP systems translates into broader organizational outcomes, offering practical implications for future ERP development and implementation strategies.